Business-to-business data sharing: An economic and legal analysis - Bertin Martens; Alexandre De Streel; Inge Graef; Thomas Tombal; Nestor Duch Brown (European Commission, Joint Research Centre (JRC), 2020)
This paper presents a legal and economic analysis of business-to-business (B2B) data markets. It starts from the economic characteristics of data and explores to what extent private B2B data markets result in a socially optimal degree of data sharing, or whether there are market failures in data markets that might justify public policy intervention. It examines the conditions under which monopolistic data market failures may occur. It contrasts these welfare losses with the welfare gains from economies of scope in data aggregation in large pools. It also discusses other potential sources of B2B data market failures due to negative externalities, risks and transaction costs and asymmetric information situations. In a next step, the paper explores solutions to overcome these market failures. Private third-party data intermediaries may be in a position to overcome market failures due to high transactions costs and risks. They can aggregate data in large pools to harvest the benefits of economies of scale and scope in data. Where third-party intervention fails, regulators can step in, with ex-post competition instruments and with ex-ante regulation. The latter includes data portability rights for personal data and mandatory data access rights.
Keywords: O22; L16; 330; data markets; data ownership and access rights